Effect of three bleaching agents on the surface properties of three different esthetic restorative materials - (:unkn) unknown (MOSBY, INC, 2003)
Statement of problem. Information related to the effect of night-guard vital bleaching procedure on the surface properties of esthetic dental restorative materials is incomplete. Purpose. The aim of this study was to examine the effects of 3 proprietary carbamide peroxide bleaching agents on the surface properties of 3 dental esthetic restorative materials. Material and methods. Three bleaching products (Nite White, Opalescence, and Rembrandt Lighten Gel) and 3 restorative materials (Duceram, Fuji II LC, and Silux Plus) were studied. A stainless steel mold and a 6-mm-thick polytetrafluoroethylene plate with a 1-cm-diameter hole were used to prepare 30 standardized specimens for each of the 3 restorative materials tested. Each group was divided into 3 subgroups (n=10). Two specimens from each subgroup were selected to form a control group. Three different carbamide peroxide bleaching agents were applied to each restorative material group for 8 hours per day for 30 days, respectively. Initial roughness measurements (Ra measured in mum) were made by use of a profilometer, at repeated intervals of 24 hours, 48 hours, 1, 2, 3, and 4 weeks (30 days). Surface topography of the specimens was assessed by scanning electron microscopy, and results were compared with the control group graphically. Surface structure and alterations of atomic weight percentages of element were made by use of energy-dispersive x-ray microanalysis. One-way analysis of variance was used to evaluate the surface roughness measurements. Significant results were evaluated with Fisher and Duncan's multiple range test (P<.005) Result. Surface roughness values for all restorative materials increased during the bleaching procedure. The only significant increase was found with the effect of Rembrandt bleaching gel on modified glass ionomer cement (mean Ra was 0.48 mum initially, 0.5 mum at 24 hours, 0.75 mum at 2 weeks, and 0.83 mum at 30 days). Surface roughness values increased significantly during the first 2 weeks (P<.005) for all bleaching groups of each restorative material, and no significant changes were seen in the following periods. SEM micrographs of the feldspathic porcelain specimens for each bleaching agent appeared to be similar to the control group. All of the modified glass ionomer specimens revealed serious cracking areas, whereas microfilled composite specimens showed increased surface porosity and cracks in certain areas when compared with control specimens. Surface spectral analyses results indicated a decrease in the SiO2 content in the feldspathic porcelain and the microfilled composite groups for all bleaching agents. Modified glass ionomer specimens bleached with Nite White and Rembrandt showed an increase in mass percentage of SiO2, whereas Opalescence specimens showed a decrease. However, there were no significant differences between the groups. Conclusion. Within the limitations of this study, no significant difference was found between bleaching agents. Most changes occurred in the first 2 weeks; the products tested were relatively stable in the following test periods. No significant change in the surface roughness of feldspathic porcelain was observed. On the other hand, the microfilled composite tested showed slight changes in the surface roughness. Significant changes were found for the modified glass ionomer cement (P>.005).
Keywords: PORCELAIN; CEMENTS; COLOR